The Energy and Carbon Footprint of an Urban Waste Collection Fleet: A Case Study in Central Italy - Alessio Quintili; Beatrice Castellani (Recycling, 2020)
Municipal solid waste collection and transport are functional activities in waste management, with a significant energy and carbon footprint and a significant effect on the urban environment. An issue related to municipal solid waste collection and transport is their regional and municipal implementation, affected by sorting and recycling strategies at local level. An efficient collection is necessary to optimize the whole recycling process. The present paper shows the results of an energy, environmental, and economic evaluation of a case study, analyzing the fleet used for municipal solid waste collection and transport in 10 municipalities in Central Italy. The current scenario was compared with alternative scenarios on the basis of some parameters for performance evaluation: vehicles’ energy consumption, carbon footprint, routes, and costs. Results show that for passenger cars, the alternative scenario based on an entire fleet of dual compressed natural gas (CNG) vehicles led to a reduction of the CO2 emissions (−2675 kgCO2eq) in the analyzed period (January–August 2019) and a reduction of the energy consumption (−1.96 MJ km−1). An entire fleet of CNG vehicles led to an increase of CO2 emissions: +0.02 kgCO2eqkgwaste−1 (+110%) for compactors (35–75 q) and +0.09 kgCO2eqkgwaste−1 (+377%) for compactors (80–180 q). Moreover, both categories report a higher fuel consumption and specific energy consumption. For waste transport high-capacity vehicles, we propose the installation of a Stop-Start System, which leads to environmental and energy benefits (a saving of 38,332 kgCO2eq and 8.8 × 10−7 MJ km−1kgwaste−1). On three-wheeler vehicles, the installation of the Stop-Start System is completely disadvantageous.